2014
DOI: 10.1016/j.jvs.2013.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Managing iliofemoral deep venous thrombosis of pregnancy with a strategy of thrombus removal is safe and avoids post-thrombotic morbidity

Abstract: Extensive DVT of pregnancy can be effectively and safely treated with a strategy of thrombus removal, resulting in a patent venous system, normal valve function in many, prevention of PTS, and reduction in recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
1
35
0
2
Order By: Relevance
“…The fetal radiation dose resulting from PCDT in the first trimester can be calculated in the range of 175-245 mGy, which is associated with a childhood cancer risk of 1.3%-2%, six to 10 times that associated with environmental/background radiation exposure. Second-or third-trimester iliofemoral DVT might be managed by PCDT with appropriate precautions such as shielding and dose-reduction techniques, or by surgical thrombectomy (12), depending on clinical severity and early response to anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal radiation dose resulting from PCDT in the first trimester can be calculated in the range of 175-245 mGy, which is associated with a childhood cancer risk of 1.3%-2%, six to 10 times that associated with environmental/background radiation exposure. Second-or third-trimester iliofemoral DVT might be managed by PCDT with appropriate precautions such as shielding and dose-reduction techniques, or by surgical thrombectomy (12), depending on clinical severity and early response to anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several options for DVT treatment: anticoagulant therapy, catheter-directed thrombolytic therapy, angioplasty and stenting (5,6). The goal of treatment is to reduce symptoms and the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, several surgical procedures have been used to correct compression, including venovenous bypass with an autologous vein, the creation of a tissue sling to elevate the overriding right iliac artery, retropositioning of the iliac artery and excision of the intraluminal spur via patch venoplasty. Recently, an important strategy has been to provide endovascular treatment or a combination of endovascular and surgical treatment (5,6). A recent report showed that these treatments decrease the incidence of DVT, known as postthrombotic syndrome (PTS), and venous obstruction compared with systemic anticoagulation (RR =0.19, 95% CI 0.07 to 0.48) (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether these treatment options are also a safe and eff ective alternative in pregnant women. In a case series, Herrera et al presented outcome data for 13 pregnant women with extensive DVT involving the iliofemoral veins who were treated with catheter-directed or pharmacomechanical thrombolysis (n = 11) or surgical (n = 2) venous thrombectomy [119]. After a mean follow-up of 1.3 years (range 1 -74 months), venous duplex ultrasound revealed patent veins in 12/13 patients (92 %) and normal valve functions in 10/13 patients (77 %).…”
Section: Therapeutic Options In Limb-threatening Dvtmentioning
confidence: 99%